The impact of oculomotor functioning on neuropsychological performance in Huntington disease. Issue 2 (7th February 2016) - Carvalho, Janessa O.; Long, Jeffrey D.; Westervelt, Holly J.; Smith, Megan M.; Bruce, Jared M.; Kim, Ji-In; Mills, James A.; Paulsen, Jane S.; the PREDICT-HD Investigators; Coordinators of the Huntington Study Group,
ABSTRACT: Huntington disease (HD) is a neurodegenerative condition with prominent motor (including oculomotor), cognitive, and psychiatric effects. While neuropsychological deficits are present in HD, motor impairments may impact performance on neuropsychological measures, especially those requiring a speeded response, as has been demonstrated in multiple sclerosis and schizophrenia. The current study is the first to explore associations between oculomotor functions and neuropsychological performance in HD. Participants with impaired oculomotor functioning performed worse than those with normal oculomotor functioning on cognitive tasks requiring oculomotor involvement, particularly on psychomotor speed tasks, controlling for covariates. Consideration of oculomotor dysfunction on neuropsychological performance is critical, particularly for populations with motor deficits.